The bilingual development of plural marking in a Malay-English child - Mohamed Salleh, Rabiah Tul Adawiyah; Di Biase, Bruno; Kawaguchi, Satomi (John Benjamins Publishing Company, 2023)
This study investigates the acquisition of plural encoding in a Malay-English bilingual first language acquirer from a Processability Theory (PT) perspective. In Malay, plurality is encoded through reduplication, while English uses morphological inflection. The child’s oral production was collected weekly from age 3;4 to 3;10 using natural conversation and elicitation tasks in separate Malay and English sessions. Expressions for singular and plural contexts are analysed based on PT. Results suggest that pluralisation in each language followed PT, they add to the applicability of PT to bilingual first language acquisition (BFLA), and reveal some novel typological sequences, Cross-linguistic influences were found in plural encodings in each language. Also, a prosodic feature usefully disambiguated between Malay ‘iteration’ (Lemma) and ‘reduplication’ (Category procedure).